Enzimi, acidi organici ed altri metaboliti coinvolti nella patogenesi di Penicillium spp - Donati, Irene <1977> (Alma Mater Studiorum - Università di Bologna, 2008)
Blue mould caused by Penicillium expansum Link is one of the most destructive rot of pome fruit in all growing areas (Snowdon, 1990; Jones and Aldwinckle, 1991; Tonini,1996) In the past, Penicillium rot has been controlled by fungicide postharvest treatment mainly by thiabendazole (TBZ) and benomyl (Hardenburg and Spalding, 1972), but their intense use produced the appearance of resistant strains with a great reduction of their activity The aims of the present study were to characterize the isolates of Pencillium sp causing blue mold on pear in Italy by physiological and biochemical parameters. In particular differencing also the behavior of isolates to relationship with sensitivity or resistance to TBZ treatments. We have examined the early stage of infection in relation to enzyme activity, local modulation of pH, production of organic acids, and to secondary metabolism of pathogen. The results described here confirm that the majority of P. expansum isolates from pears packing houses are resistant to TBZ, Among the TBZ-resistant isolates scored in this work, different isolates (RR) showed higher percentage of conidial germination on TBZ-amended medium compared to non amended medium. This may indicate a stimulatory effect of TBZ on conidial germination. Therefore TBZ treatments are not only ineffective for controlling P. expansum, but they may also increase the severity of blue mould on fruits. In the absence of fungicide, isolates showed a significant difference for infection severity, R and RR isolates are characterized by higher pathogenic fitness on fruits, producing larger lesions than S isolates. These data are supported by the study with laboratory-induced resistant isolates, which shows the lack of correlation between TBZ resistance and osmotic sensitivity, and highlights the association between TBZ resistance and infection severity (Baraldi et al 2003). Enzymatic screening gave a positive reaction to esterase, urease, pectinase activity, in addition, the pathogen is able to synthesize a complex enzyme act to degrade the main components of the cell wall especially pectin and cellulose. Isolated sensitive and resistant are characterized by a good activity of pectinase, especially from poligactoronase, which, as already reported by several studies (D'hallewin et al, 2004; Prusky et al, 2004), are the basis of degradative process of cell wall. Also, although the measure was minor also highlighted some activities of cellulase, but even note in the production of this kind of cellulase and hemicellulase P. Expansum were not targeted, studies have found no other source of information in this regard. Twenty isolates of Penicillium expansum, were tested in vitro ad in vivo for acid production ability and pH drop. We have found that modulation of pH and the organic acids extrusion were influence to various parameter:  Initial pH: in general, the greatest reduction of pH was observed in isolates grown at pH 7, except for four isolates that maintained the pH of the medium close to 7, the others significantly decreased the pH, ranging from 5.5 to 4.1.. In extreme acid condition (pH 3,0) growth and modulation of pH is most lower respect optimal condition (pH 5,0). Also isolates R and RR have showed a greater adaptation to environmental condition more than isolates S.  Time: although the acidification continues for some days, PH modulation is strongest in early hours (48-72 hours)of inoculation process. Time also affects the quality of organic acids, for example in vitro results showed an initial abundant production of succinc acid, followed to important production of galacturoinc acid.  Substrates: there are many differences for the type of acids produced in vitro and in vivo. Results showed in vivo an abundant production of galacturonic, malic, and citric acids and some unknown organic acids in smaller concentrations. Secondary metabolite analysis revealed intra-specific differences, and patulin was found in all isolates, but most significant reduction was observed between in vitro and in vivo samples. There was no correlation between the concentration of patulin, and the percentage of infected fruits, but sample with a lower infection severity of rotten area than the others, showed a significantly lower mycotoxin concentration than samples with a higher lesion diameter of rotten area. Beyond of patulin was detected the presence of another secondary metabolite, penitrem A.